Use of different devices for surgical treatment of proximal humerus fractures in adults: a systematic review - Pavone, Vito; Vescio, Andrea; Denaro, Regina; Costa, Danilo; Condorelli, Giuseppe; Caruso, Vincenzo Fabrizio; Sessa, Giuseppe; Testa, Gianluca (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Proximal humeral fracture is one of the most common osteoporotic fractures in elderly people. The proper treatment choice is controversial. Open reduction and internal fixation (ORIF) with plate and screws is currently the most common treatment for the majority of displaced proximal humeral fractures. The aim of this systematic review is to investigate the surgical treatment outcomes of PHFs, focusing on main used devices and surgical approaches.Methods: From the earliest record up to 21 July 2020, two independent authors conducted a systematic review of two medical electronic database (PubMed and Science Direct). To achieve the maximum sensitivity of the search strategy, the following terms were combined: “(proximal NOT shaft NOT distal) AND humeral AND fracture AND (plate OR locking plate OR osteosynthesis NOT nail NOT arthroplasty)” as either key words or MeSH terms. The risk of bias of the included studies was assessed, agreeing to the Cochrane Handbook guidelines.Results: Thirty-four articles were initially noticed after the term string research in the two electronic databases. Finally, after full-text reading and analyzing the reference list, 8 studies were selected. The mean age recorded was 69.5 years (Range 67-72). All the studies included two-, three-, four-fragments fracture. Seven studies investigated PHILOS (Synthes, Bettlach, Switzerland) implants results, while one investigated CFR-PEEK plate (PEEK Power Humeral Fracture Plate; Arthrex, Naples, Florida, USA) outcomes or other plates. Deltopectoral and Transdeltoid approaches were the more common used.Conclusions: Both deltopectoral and transdeltoid approaches are valid approach in plating after proximal humerus fractures, for these reasons, the surgeon experience is crucial in the choice. The more valid implant is still unclear. The develop of prospective randomized comparative studies is strongly encourages.